Penerapan Strategi Pembelajaran Bermain Peran dalam Meningkatkan Motivasi dan Prestasi Belajar IPA Siswa - Hartaty (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
This study aims to determine the Application of Role-Playing Learning Strategies in Improving Motivation and Science Learning Achievement of Class VII-3 Students of SMP Negeri 1 Brang Rea. The type of research used is classroom action research (CAR) with an experimental approach because the symptoms that arise deliberately are learning by playing a role on motivation and science learning achievement, the research was carried out on class VII-3 students of SMP Negeri 1 Brang Rea in 2020/2021 lessons. From the results of the study, it was found that there was an increase between cycle 1 to cycle II, both the highest, lowest, average, and standard deviation values. This shows that teaching with the role-playing method can improve student achievement, especially students in grades VII-3 of SMP Negeri 1 Brang Rea. where the learning completeness obtained in the first cycle, namely 54.54% can be said to have not been achieved or completed, the second cycle = 86.36% has been completed because it has reached the set target, which is at least 75% of the number of students who get a score or equal to 75. From this also it can be said that there is an increase in classical learning completeness between cycle I to cycle II. Thus, learning with the role-playing method can complete learning outcomes, especially for class VII-3 students of SMP Negeri 1 Brang Rea for the 2020/2021 school year.